1996
DOI: 10.1111/j.1432-1033.1996.0272n.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipopolysaccharides of Polymyxin‐Resistant and Polymyxin‐Sensitive Klebsiella pneumoniae O3

Abstract: Lipopolysaccharides isolated from the polymyxin-resistant Klebsiella pneumoniue 0 3 mutant OM-5 and its polymyxin-sensitive parent LEN-1 were analyzed for chemical composition, and their lipid A portions were structurally characterized. The lipopolysaccharide of OM-5 contained approximately five times more 4-amino-4-deoxy-~-arabinopyranose than that of LEN-1. Other saccharide and phosphate components exhibited no significant differences. Structural characterization, including analyses by phosphorus magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 41 publications
6
91
0
1
Order By: Relevance
“…Ion m/z 1,797 has been previously detected in Klebsiella lipid A and is consistent with two glucosamines, two phosphates, four R-3-hydroxymyristoyl primary acyl chains, and one myristate (C 14 ) and one laureate (C 12 ) as the secondary acyl chains (Fig. 2) (15,16,20,21).…”
Section: Significancementioning
confidence: 82%
See 1 more Smart Citation
“…Ion m/z 1,797 has been previously detected in Klebsiella lipid A and is consistent with two glucosamines, two phosphates, four R-3-hydroxymyristoyl primary acyl chains, and one myristate (C 14 ) and one laureate (C 12 ) as the secondary acyl chains (Fig. 2) (15,16,20,21).…”
Section: Significancementioning
confidence: 82%
“…The fact that the lipid A from the lpxM mutant contained 2-hydroxymyristate both in vivo and in vitro (m/z 1,630 and m/z 1,866) strongly suggests that Klebsiella LpxO (KpLpxO) hydroxylates the myristate (C 14 ) on the primary 2′-linked R-3-hydroxymyristoyl group. Mass spectrometry analysis has previously shown that the nonreducing glucosamine of Klebsiella lipid A is substituted with only one (amide-linked) R-3-hydroxymyristoyl group further acylated with myristate (C 14 ) or 2-hydroxymyristate (C 14:OH ) (20,21). In good agreement, we show that KpLpxO hydroxylated Yersinia enterocolitica O:8 myristate (C 14 ) on the primary 2′-linked R-3-hydroxymyristoyl group (peaks m/z 1,404 and m/z 1,813; SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…These molecules often act via a combination of their positive charge, which enables them to interact with anionic molecules on the bacterial surface, in combination with their hydrophobic character, which results in a disruption of the bacterial membrane (54,55). The LPS is the target molecule of defensins in Gram-negative bacteria, and bacteria that are resistant acquire this resistance by modification to their LPS structures (56 -60); perhaps, one of the best known examples is the resistance acquired through the addition of aminoarabinose and ethanol amine groups to the LPS of S. typhimurium (57)(58)(59)(60). Because of the structural alteration of the LPS during bacteroid formation, bacteria and bacteroids were compared for their resistance to poly-L-lysine, polymyxin B, and melittin.…”
Section: Discussionmentioning
confidence: 99%
“…A PmrA-PmrB TCS, dealing with cationic antimicrobial peptides and polymyxin resistance in pathogens (6), is responsible for sensing the external stimuli caused directly or indirectly by excess Fe 3ϩ , low Mg 2ϩ , and mild acidic environments (7)(8)(9). Under this TCS, pathogens can alter the composition of their cell walls to resist neutralization of polymyxin for drug resistance and allow bacterial survival within macrophages by reducing the affinity with cationic antimicrobial peptides (10,11).…”
mentioning
confidence: 99%